1992
DOI: 10.1113/jphysiol.1992.sp019216
|View full text |Cite
|
Sign up to set email alerts
|

Induction of haemodynamic oscillations in the perfused rat liver by K+ channel blockers.

Abstract: SUMMARY1. Exposure of the isolated perfused (constant flow) rat liver to the K+ channel blockers 4-aminopyridine (4-AP) or Cs+ causes the appearance of oscillations in portal pressure and oxygen uptake. The oscillations have a mean frequency of 0 035 Hz (2-1 cycles/min) and are fully reversible upon perfusion with blocker-free saline. Tetraethylammonium (0-17-24-7 mM) does not induce oscillatory behaviour.2. Reversible block of the 4-AP-induced oscillations is caused by 2 mM-EGTA, or verapamil, chlorpheniramin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…In an earlier report we showed that 4-aminopyridine (4-AP) causes the appearance of oscillations in portal pressure and effluent 02 concentration of 0-6 mmHg and 6 AM 0 within 5 min of infusion, and having a frequency of 0-035 Hz (Hill & Ajikobi, 1992). The differences between the 4-AP-and Cs+-induced oscillations are discussed in terms of tetrodotoxin (TTX) sensitivity, and waveform and frequency, with the aim of differentiating between the primary mechanism and site of action of these two K+ channel blockers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In an earlier report we showed that 4-aminopyridine (4-AP) causes the appearance of oscillations in portal pressure and effluent 02 concentration of 0-6 mmHg and 6 AM 0 within 5 min of infusion, and having a frequency of 0-035 Hz (Hill & Ajikobi, 1992). The differences between the 4-AP-and Cs+-induced oscillations are discussed in terms of tetrodotoxin (TTX) sensitivity, and waveform and frequency, with the aim of differentiating between the primary mechanism and site of action of these two K+ channel blockers.…”
Section: Discussionmentioning
confidence: 99%
“…First, the fast Na+ channel blocker TTX reversibly blocks the Cs+-induced oscillations but not those caused by 4-AP (Hill & Ajikobi, 1992). TTX-sensitive Na+ channels are not present in endothelial cells derived from different tissues (Adams, Barakeh, Laskey & Van Breeman, 1989), or smooth muscle cells from the portal vein (Hume & LeBlanc, 1989) and other vascular sources (Van Breeman & Saida, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations